MAPPING CRITICAL KNOWLEDGE USING DIGITAL TOOLS AND THE RELATIONSHIP WITH THE DIGITAL HUMANITIES - Coneglian Junior, Deunezio [UNESP]; Geraldo, Genilson; Bisset-Alvarez, Edgar (Univ Murcia, 2023)
This study aimed to present the application of the Analytic Hierarchy Process (AHP) and Social Network Analysis (SNA) methodologies, as reliable and dynamic means to map knowledge, in order to answer how to identify, prioritize and map a truly critical knowledge for an organization in an agile and reliable manner? seeking to understand this process within the Digital Humanities phenomenon. Thus, this study is characterized as an exploratory research, since it knows, analyzes, and uses the premises of the AHP and ARS methods and, in this sense, recognizing its investigative procedures, as a documental research. This study concludes that, by means of Critical Knowledge Mapping using computational resources, it is possible to identify and locate relevant knowledge, grouping it by area, generating complete maps of the entire organization, thus making knowledge management an efficient and collaborative process for conducting business strategy.
Keywords: Mapping of critical knowledge; Digital tools; Knowledge Management; Digital Humanities; Information